Engaging Dairy Farmers in Safety Messages: Values, Moral Norms, Barriers, and Implications for Communication - Emily Wilmes; Rebecca Swenson (Journal of Applied Communications, 2019)
Dairy farms pose many hazards to farmers and their employees, including the risk of injury caused by handling animals. On many farms, there is a lack of consistent information and training related to farm safety topics, including stockmanship, or safe animal handling. The purpose of this qualitative research was to explore effective communication strategies that support the application of stockmanship practices and more broadly support health and safety measures and the adoption of new behaviors by farmers and their employees. Research was conducted in three stages via in-depth farm tours and in-person interviews, a qualitative survey, and follow-up phone interviews with dairy farmers. Findings identified four values and moral norms important to dairy farmers and four barriers to implementation of farm safety practices. The research also revealed publications and in-person meetings as key channels of communication and on-farm consultants as important influencers. From the research findings, three major recommendations emerged. These include using a train the trainer educational model, engaging with professionals and encouraging farmer-to-farmer communication, and leveraging digital resources.
Keywords: dairy farmers; stockmanship; safety communication; employee training; engagement